(untitled) (Web of Teachers: Inderscience Research, 2024)
This article reveals the role and importance of investments in the development of the national economy, analyzes the trends of attracting investments, and distinguishes the principles of investment policy. Also, the role of securities in the export and import of the country was analyzed based on practical data.